1977
DOI: 10.1093/jnci/58.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Breast Cancer Between Japan and the United States 2

Abstract: Two surgically treated series of 375 Japanese and 352 American women with breast cancer were compared with respect to overall survival and recurrence-free survival rates. Recurrence-free survival rates in Japanese women were superior to those in American women. Overall survival rates were also better in Japanese women, although the difference was not nearly as great as for recurrence-free survival. This seemed due to an improved survival after metastasis in the American women. In analyzing recurrence-free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The incidence and prognosis of breast cancer differs between Western and Japanese women [30][31][32] [44] found that indomethacin inhibited growth of cultured human mammary fibroadenoma cells and that this inhibition was not reversed by prostaglandin E2. In an in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and prognosis of breast cancer differs between Western and Japanese women [30][31][32] [44] found that indomethacin inhibited growth of cultured human mammary fibroadenoma cells and that this inhibition was not reversed by prostaglandin E2. In an in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…These studies include nutritional epidemiologic analysis, migrant studies, time-trend studies, retrospective case-control studies, and analyses of populations with distinct nutritional intakes [2,6,9,17,19,20,27,31]. A variety of animal studies also support an association between dietary fat intake and mammary cancer development [10,16,28].…”
Section: Introductionmentioning
confidence: 99%
“…These observations might well be linked with a number of reports relating nutritional factors with tumor behavior after diagnosis (e.g., Morrison et al [8] and Nemoto et al [9] have reported a worse prognosis of breast cancer in American women than in Japanese women) and with other reports documenting the adverse role of overweight in breast cancer survival [10][11][12].…”
Section: Nutrition and The Growth Rate Of Breast Cancermentioning
confidence: 72%